Dynamic origins of substrate promiscuity in bacterial galactokinases. (1st December 2019) - McAuley, Margaret; Huang, Meilan; Timson, David J.
Abstract: Galactokinase catalyses the ATP-dependent phosphorylation of galactose and structurally related sugars. The enzyme has attracted interest as a potential biocatalyst for the production of sugar 1-phosphates and several attempts have been made to broaden its specificity. In general, bacterial galactokinases have wider substrate ranges than mammalian ones. The enzymes from Escherichia coli and Lactococcus lactis have received particular attention and a number of variants with increased promiscuity have been identified. Here, we present a molecular dynamics study designed to investigate the molecular causes of the wider substrate ranges of these enzymes and their variants with particular reference to protein mobility. Some regions close to the active site of the enzyme have different structures in the bacterial enzymes compared to the human one. Alterations known to increase the substrate range (e.g. Y371H in the E. coli enzyme), tend to alter the conformation of a key α-helical region (residues 216–232 in the E. coli enzyme). The equivalent helix in the human enzyme has previously been predicted to be altered in variants which affect catalytic activity or protein stability. This helix appears to be a key region in galactokinases from a range of species and may represent an interesting target for future attempts to broaden the specificity of galactokinases. Graphical abstract: Image 1 Highlights: Bacterial galactokinases are typically more promiscuous than mammalian ones. A key α-helix in human galactokinase is important in controlling specificity. The mobility of the equivalent helix in the bacterial enzyme was investigated. This region is predicted to be important in the wide specificity of these enzymes. Therefore, it could be altered to further expand the substrate range.